A new integration method with minimized extra coupling effects using inductor and capacitor series-parallel compensation for wireless EV charger. (1st December 2017) - Deng, Junjun; Pang, Bo; Shi, Wenli; Wang, Zhenpo
Highlights: A magnetic integration method is presented for wireless EV charger. The impact of the extra couplings on the characteristic is analyzed quantitatively. The extra couplings between compensated coils and main coils are minimized. The unipolar type and the bipolar type as the compensated coils are compared. Abstract: Wireless electric vehicle charger has become increasingly popular because of its improved convenience and safety. The recently proposed inductor-capacitor-capacitor (LCC) compensated topology and bipolar magnetic coupler structure have promoted the comprehensive performance of the wireless power transfer (WPT) system. Furthermore, the idea of integrating the magnetic components in the LCC compensated WPT system has been proposed for reducing the bulk. However, the extra inter-couplings between the adjacent coils are also introduced, which complicates the parameters design and the characteristic analysis. In this paper, a new integration method is presented for wireless EV charger adopting LCC compensation networks along with bipolar coupler. The impact of the extra couplings is evaluated thoroughly through the circuit analysis and simulation. The finite element analysis (FEA) tool is utilized to evaluate the extra coupling effects of the compensated coils, which leads to the proposed integration coupler structure. The comparison of the unipolar and the bipolar as the compensated coils for the extra coupling minimizing is discussed considering the misalignment. At last, a prototype of the magnetic coupler with a size of 550 mm × 500 mm has been built and tested. A peak efficiency of 95% is achieved while transferring 6.6 kW electric power from a DC power source to the load in the condition of 150 mm vertical clearance.